الذكاء اللغوي في تعلم اللغة لتلاميذ الفصل الرابع بمدرسة هاشم أشعري الابتدائية مالانج - Asih, Nur Fitri (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
The purpose of this study was to determine the level of language intelligence in language learning of grade IV students of MI Hasyim Asy'ari Malang. This study used a quantitative approach. The population in this study was all grade IV students of MI Hasyim Asy'ari Malang which amounted to 93 students, while the sample of the study was the entire population, namely students of grade IV A, B and C MI Hasyim Asy'ari Malang. Data collection techniques in this study through questionnaires. The source of data in this study is primary data obtained directly from students. Furthermore, the data that has been obtained is then analyzed using descriptive statistical analysis. The results of this study showed that the level of language intelligence of grade IV students of MI Hasyim Asy'ari Malang was in the medium category as many as 57 out of 93 students with a percentage of 60% with a total average score of 80.